Lost in the chaos: Flawed literature should not generate new disorders: Commentary on: Chaos and confusion in DSM-5 diagnosis of Internet Gaming Disorder: Issues, concerns, and recommendations for clarity in the field (Kuss et al.) - Van Rooij, Antonius J. (J Behav Addict, 2017)
The paper by Kuss, Griffiths, and Pontes (2016) titled “Chaos and confusion in DSM-5 diagnosis of Internet Gaming Disorder: Issues, concerns, and recommendations for clarity in the field” examines issues relating to the concept of Internet Gaming Disorder. We agree that there are serious issues and extend their arguments by suggesting that the field lacks basic theory, definitions, patient research, and properly validated and standardized assessment tools. As most studies derive data from survey research in functional populations, they exclude people with severe functional impairment and provide only limited information on the hypothesized disorder. Yet findings from such studies are widely used and often exaggerated, leading many to believe that we know more about the problem behavior than we do. We further argue that video game play is associated with several benefits and that formalizing this popular hobby as a psychiatric disorder is not without risks. It might undermine children’s right to play or encourage repressive treatment programs, which ultimately threaten children’s right to protection against violence. While Kuss et al. (2016) express support for the formal implementation of a disorder, we argue that before we have a proper evidence base, a sound theory, and validated assessment tools, it is irresponsible to support a formal category of disorder and doing so would solidify a confirmatory approach to research in this area.